Applesnails (of Florida), Pomacea spp. (Gastropoda: Prosobranchia: Pilidae) - Lionel A. Stange (EDIS, 2005)
There are three species of applesnails in Florida. One is native and the others are introduced. The Florida applesnail, Pomacea paludosa, occurs throughout peninsular Florida (Thompson 1984). It is the principal food of the Everglades Kite (Rostrhamus sociabilis plumbeus Ridgway) and thus should be considered beneficial. The spiketopped applesnail, Pomacea bridgesi, was introduced many years ago into South Florida. However, it is the third species of Pomacea, P. canaliculata, that has caused recent concern to agriculture. This species grows nearly twice the size as the other two species and has become a serious rice pest in many countries. This document is EENY-323 (originally published as DPI Entomology Circular 388), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2004.